ChemInform Abstract: Afterglow Luminescence Properties and Mechanism of Novel Orange Afterglow Phosphor: Ca2Sb2O7:Sm3+. Issue 47 (4th November 2013) - Shi, Liurong; Zhang, Jiachi; Li, Huihui; Feng, Pengfei; Liu, Xue; Fu, Zhongqiu; Wang, Yuhua
Abstract A series of Sm‐doped Ca2Sb2O7 samples is prepared by solid state reaction of CaCO3, Sb2O3, and Sm2O3 (air, alumina crucible, 1150 °C, 16 h).